Paradigma Tiga Tipe Hukum Menurut Philippe Nonet dan Philippe Selznick dalam Kaitannya dengan Pengelolaan Negara: Pendahuluan, pembahasan, kesimpulan, - Yusran Sibawaih; Dwi Ambarwati (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2025)
Indonesia has is the law, that puts the law as the basis of our nation and state.In practice, law not only function as an organ of officers, but also as a means of creating social justice.But, political influence, power, and interest groups often cause an imbalance in application of the law.This study adopting the literature study to assess typologies law according to philippe nonet selznick and philip, that divides into three type: repressive law, autonomous, and responsive. The result showed that type of repressive tend to put law as an instrument of rule; type autonomous stressed the independence of the law from political power; while demanding responsive type of adaptive and accommodating the dynamics of social.The law responsive is considered to be the most relevant in the context of the modern state of substantive justice because it can accommodate, but the law has three type interconnected correlation and see properly applied for a reasonable limit in the management of the state.